Pembuatan Animasi 2 Dimensi Film Pendek “Phantom” Menggunakan Teknik Tweening - Aulia Nanda Rusanti; Agusdi Syafrizal; Subhan Hartanto (CV MEDAN TEKNO SOLUSI, 2024)
The rapid advancement of technology in the entertainment industry includes the field of animation. One popular form of animation is 2D animation, which effectively conveys messages to viewers. Tweening is a technique commonly used in 2D animation, allowing smooth transitions between keyframes. This technique will be applied in a short 2D animated film titled “Phantom.” The film tells the story of a student named Silver who experiences bullying during school, accompanied by a growing shadow with each instance of mistreatment. These experiences take a toll on Silver’s physical and psychological well-being. The research aims to explore the implementation of tweening techniques in 2D animation and deliver a moral message to the audience. By following the Multimedia Development Life Cycle (MDLC) approach, this animation succeeded in applying tweening techniques in animation as well as providing a moral message and entertainment with an assessment result of 87%, 88% for the assessment of understanding the moral message and 86% for the assessment of entertainment.